2019
DOI: 10.1007/s12046-019-1114-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of exit Burr in drilling of Ti6Al4V alloy

Abstract: Burrs affect precision components and cause assembly related problems, and in general, decrease manufacturing productivity. Drilling burr formation involves multiple stages that are influenced by variation in thrust forces, temperature, stress conditions, and deformation modes in the unsupported length of the workmaterial below the drill. Several of these have not been adequately investigated so far. Therefore, the objective of this work is to model the complex phenomena that occur just before the exit of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Studies have shown that the change allowed for a significant reduction in the size of burrs ( Figure 11 ). The results obtained are in line with the models presented by Rana et al [ 12 ] and Mittal et al [ 13 ].…”
Section: Results and Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that the change allowed for a significant reduction in the size of burrs ( Figure 11 ). The results obtained are in line with the models presented by Rana et al [ 12 ] and Mittal et al [ 13 ].…”
Section: Results and Analysissupporting
confidence: 92%
“…As noted by Rimpault et al [ 11 ], there is a correlation between the values of these forces and the size of burrs formed. Analytical model of burr formation in Ti-6Al-4V alloy and its experimental verification was already presented in great detail by Rana et al [ 12 ]. Another model (specific for high-speed microdrilling) was developed by Mittal et al [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the formation process of burrs is a necessary premise to control and minimize burrs, and it has certain guiding significance for exploring active burr suppression methods. The analytical method is currently the main method for people to analyze the burr formation mechanism and explore the relationship between cutting variables and burr geometry [5]. Zhang et al [6] investigated the burr formation mechanism in micro end milling by considering the minimum chip thickness, as well as the size effect of cutting edge radius.…”
Section: Introductionmentioning
confidence: 99%